H2 evolution through solar guided water splitting using Fe based composite electrode. (2021) - Das, Jagat; Sahu, Partha Pratim; Deb, Pritam
Abstract: Artificial photosynthesis based on solar guided water splitting is essential to obtain green renewable energy sources which is a potential replacement of fossil fuels. This paper presents a water splitting design with proper choice of non-precious and easily available composite metal (Fe, Ni, Mn and Al) based electrode to evolve the cleanest form of H2 and O2 separately through water electrolysis with a low voltage of 1.6 V using NaOH electrolyte of pH 12.7. The power supply embedded with solar panel connecting to the electrodes (anode/cathode) is maintained at a voltage level of 1.5–5 V in order to initiate the electrolysis process (electrolyte NaOH, pH = 12.7). This process leads to movement of H + and OH − ions to cathode and anode kept within the gas chambers and the H2 gas evolved is stored. Experimental results show a high rate of H2 evolution that falls in the range of (7.3 × 10 15 to 37.3x 10 15 ) molecules s −1 and current density is found to be 2.6 mA cm −2 at 1.6 Volt which is far better than that of many state-of-the-art techniques. The proposed design setup along with the composite materials based electrode, produces a high rate of Hydrogen gas from H2 O with high current density in low voltage.